86.3k views
0 votes
The functions f and g are defined as follows.

f (x) = 3x^2 - 3x g (x) = 3x -1
Find f(-4) and g(-6)

Simplify your answers as much as possible.

User Tturbo
by
4.8k points

2 Answers

2 votes

Answer:

f(-4)=60 and g(-6)=17

Explanation:

f(x)

Plug in -4 for x-values

  • 3(-4)^2 - 3(-4)

Square -4

  • 3(16) - 3(-4)

Multiply 3 by 16 and -3 by -4 then solve

  • 48+12=60

Simplify

  • f(-4)=60

g(x)

Plug in -6 for x

  • -3(-6)-1

Multiply -3 by -6

  • -3(-6)=18

Subtract 1

  • 18-1=17

Simplify

  • g(-6)=17
User Ajesamann
by
5.8k points
6 votes

For this case we have the following functions:


f (x) = 3x ^ 2-3x\\g (x) = 3x-1

We must find the value of the function
f (x) when
x = -4, then:


f (-4) = 3 (-4) ^ 2-3 (-4)\\f (-4) = 3 * 16 12\\f (-4) = 48 12\\f (-4) = 60

We must find the value of the function g (x) when
x = -6, then:


g (-6) = 3 (-6) -1\\g (-6) = - 18-1\\g (-6) = - 19

Answer:


f (-4) = 60\\g (-6) = - 19

User Jordi Bruin
by
5.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.